Propuesta de un plan para el manejo adecuado de los desechos sólidos domiciliarios en el cantón Nangaritza, provincia de Zamora Chinchipe - Lupercio Viñan, Yennifer Alexandra (2016)
This research work was conducted in the canton Nangaritza, is a proposal of a plan for the proper management of household solid waste produced in the county; This work is structured by the following parts: a (selection of literature; b) methodology; c) results; d) proposal. In regard to the review of literature contains the basic concepts that serve as argument to develop the work, also this argument is essential to make the discussions and conclusions, this literature was selected according to the subject on waste management Nangaritza solids in the canton. The methodological part is also very important because it indicates the way forward, is the guide to achieve the objectives, therefore made use of the scientific method, as well as other techniques such as observation, survey, interview and other instruments needed to gather field information. This research is descriptive allowing the current status of solid waste management and thereby make the respective analysis and determine numerical values of percapita production, production of organic and inorganic waste. Among the most important results we found it was determined that the current structure of GAD should be reorganized at the level of the Environmental Management Unit, and also must train staff of this unit; Another finding is to seek the promotion of environmental culture of the population which can improve waste management. Finally, the proposal has been prepared based on the results of the diagnosis, ie knowing the current situation on the management of solid waste in the canton and thereby developing the proposal that may lead to better treatment, use of them in function of each day contribute to the decontamination of the environment and thus achieve better days for society.